Switched mode power supply for welding equipment - Soojarv, J.; Dragunov, V. (Elektronika ir Elektrotechnika, 1998)
This paper presents the development of a switched-mode power supply for welding equipment with the power rating of 10kW. Application of IGBT intelligent power modules and modern pulse width modulators allows to reduce the size and weight of the power supply, improve reliability and dynamic response of the system. But special circuit layout and simulation considerations must be followed.